Endometrial stromal sarcoma: a rare tumour - Kaur, Amrit Pal; Shergill, Harbhajan Kaur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Endometrial stromal sarcomas (ESS) are rare endometrial tumours arising from stroma of endometrium i.e. connective tissue of endometrium rather than glands. Usually a pre-operative diagnosis is difficult. Total abdominal hysterectomy with bilateral salpingo-oophorectomy is main line of treatment. Adjuvant hormone therapy in the form of progesterones, GnRH analogues, aromatase inhibitors are effective for prevention of recurrences as these tumours are invariably positive for oestrogen & progesterone receptors. Surgical excision, radiotherapy, hormone therapy are recommended for recurrences. We report a 52 yrs widow with undifferentiated endometrial stromal sarcoma weighing 3.75 kg with a short history of 3 months diagnosed only after histopathology.